SOCIOCULTURAL TRANSFORMATIONS AS A CULTURAL AND HISTORICAL PHENOMENON OF POSTMODERN SOCIETY - Mirzaulukova, F (Uzbekistan Open Conference, 2025)
The report discusses the creation concept of sociocultural transformations and their periodization in the style of eras, as well as the concept of worldview, what it is in scientific life, in moments of crisis and its stages. Its features in postmodern society, the social consequences of cultural transformations, and problems for determining the place of sociocultural transformations.
Keywords: sociocultural transformations; transitional eras; paradigmatic foundations; late Hellenism; worldview